2015
DOI: 10.1002/lary.25449
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive load in distributed and massed practice in virtual reality mastoidectomy simulation

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 19 publications
2
61
1
Order By: Relevance
“…Bjerrum et al [10] explored practice distribution, but only with flexible bronchoscopy, and found no significant differences between the 2 groups with regard to their subsequent performance on the simulator. This finding contradicts other studies which have demonstrated that distributing learning over a longer period of time proved highly efficient [45][46][47] . However, the study by Bjerrum et al [10] used only the insensitive simulator metrics, which could explain the negative findings.…”
Section: Discussioncontrasting
confidence: 56%
“…Bjerrum et al [10] explored practice distribution, but only with flexible bronchoscopy, and found no significant differences between the 2 groups with regard to their subsequent performance on the simulator. This finding contradicts other studies which have demonstrated that distributing learning over a longer period of time proved highly efficient [45][46][47] . However, the study by Bjerrum et al [10] used only the insensitive simulator metrics, which could explain the negative findings.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to this finding, the cognitive load estimated by reaction time measurement had returned to pretraining levels (distributed practice group: mean pretraining relative reaction time, 1.42 [95% CI, 1.37-1.47]; and massed practice group: mean pretraining relative reaction time, 1.34 [95% CI, 1.28-1.40]). 19 Moreover, the skills of the massed practice group were less consolidated, and the participants in this group seemed to use more time within the allowed timeframe during retention testing to achieve a similar performance. During the retention procedures, the participants in general had a poorer performance compared with end-of-training procedures in adequately defining the outer boundaries of the procedure, often violating the facial nerve, and not exposing the facial recess sufficiently, suggesting that these items could be emphasized in future instructions.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, participants were tested on their reaction time while performing a secondary task provided by the simulator at baseline and several times during the procedure to estimate the cognitive load by the increase in reaction time during simulation relative to baseline measurements. 19 The outcomes (final-product performance and relative reaction time for cognitive load estimation) were analyzed as previously described 18 to ensure comparability with previous studies. Supplemental analyses of the volume removed during VR simulation sessions were performed for this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations